MENELADANI YESUS DALAM MENDIDIK : KONSELOR YANG BERHIKMAT DI JEMAAT GMIST BAITANI BEBALI - Dikson Tatipang; MilitiaChristy Karin Pay; Frisca Elisabeth Londo (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2024)
In the world of education and counseling, the role of teachers and counselors is crucial in guiding individuals to reach their fullest potential. Jesus Christ, as the Great Teacher and Divine Counselor, sets an extraordinary example through His teachings and actions, which are filled with wisdom, love, and patience. This article explores the principles that can be learned from Jesus in the context of education and counseling, focusing on His profound wisdom in guiding, teaching, and providing counsel that addresses the inner needs of individuals. Through a holistic approach, Jesus not only offers practical solutions but also healing that encompasses physical, emotional, and spiritual aspects. The research method used in this article is qualitative research with a literature study. It is hoped that by emulating the wisdom of Jesus, educators and counselors can provide more effective, loving, and transformational guidance in the lives of the individuals they serve, amidst the growing complexities of modern times.